Let's solve each inequality step by step to find their solutions.
1. Solve \( \frac{2}{5}x - \frac{4}{5} \geq 1 \frac{1}{5} \)
Convert \( 1 \frac{1}{5} \) to an improper fraction:
\[
1 \frac{1}{5} = 1 + \frac{1}{5} = \frac{5}{5} + \frac{1}{5} = \frac{6}{5}
\]
Now, the inequality becomes:
\[
\frac{2}{5}x - \frac{4}{5} \geq \frac{6}{5}
\]
Add \( \frac{4}{5} \) to both sides:
\[
\frac{2}{5}x \geq \frac{6}{5} + \frac{4}{5}
\]
\[
\frac{2}{5}x \geq \frac{10}{5}
\]
\[
\frac{2}{5}x \geq 2
\]
Multiply both sides by \( \frac{5}{2} \) (which is positive, so the inequality remains the same):
\[
x \geq 2 \cdot \frac{5}{2}
\]
\[
x \geq 5
\]
2. Solve \( \frac{3}{7}x + \frac{1}{7} \leq 1 \frac{6}{7} \)
Convert \( 1 \frac{6}{7} \) to an improper fraction:
\[
1 \frac{6}{7} = 1 + \frac{6}{7} = \frac{7}{7} + \frac{6}{7} = \frac{13}{7}
\]
Now, the inequality becomes:
\[
\frac{3}{7}x + \frac{1}{7} \leq \frac{13}{7}
\]
Subtract \( \frac{1}{7} \) from both sides:
\[
\frac{3}{7}x \leq \frac{13}{7} - \frac{1}{7}
\]
\[
\frac{3}{7}x \leq \frac{12}{7}
\]
Multiply both sides by \( \frac{7}{3} \):
\[
x \leq \frac{12}{7} \cdot \frac{7}{3}
\]
\[
x \leq 4
\]
3. Solve \( \frac{1}{5}x - \frac{3}{5} \leq \frac{2}{5} \)
Add \( \frac{3}{5} \) to both sides:
\[
\frac{1}{5}x \leq \frac{2}{5} + \frac{3}{5}
\]
\[
\frac{1}{5}x \leq \frac{5}{5}
\]
\[
\frac{1}{5}x \leq 1
\]
Multiply both sides by \( 5 \):
\[
x \leq 5
\]
4. Solve \( \frac{3}{5}x + \frac{2}{5} \geq 3 \frac{2}{5} \)
Convert \( 3 \frac{2}{5} \) to an improper fraction:
\[
3 \frac{2}{5} = 3 + \frac{2}{5} = \frac{15}{5} + \frac{2}{5} = \frac{17}{5}
\]
Now, the inequality becomes:
\[
\frac{3}{5}x + \frac{2}{5} \geq \frac{17}{5}
\]
Subtract \( \frac{2}{5} \) from both sides:
\[
\frac{3}{5}x \geq \frac{17}{5} - \frac{2}{5}
\]
\[
\frac{3}{5}x \geq \frac{15}{5}
\]
\[
\frac{3}{5}x \geq 3
\]
Multiply both sides by \( \frac{5}{3} \):
\[
x \geq 3 \cdot \frac{5}{3}
\]
\[
x \geq 5
\]
Summary of Results
- \( \frac{2}{5}x - \frac{4}{5} \geq 1 \frac{1}{5} \) results in \( x \geq 5 \)
- \( \frac{3}{7}x + \frac{1}{7} \leq 1 \frac{6}{7} \) results in \( x \leq 4 \)
- \( \frac{1}{5}x - \frac{3}{5} \leq \frac{2}{5} \) results in \( x \leq 5 \)
- \( \frac{3}{5}x + \frac{2}{5} \geq 3 \frac{2}{5} \) results in \( x \geq 5 \)
Final Answers
- The first and fourth inequalities give the same condition: \( x \geq 5 \).
- The second inequality gives \( x \leq 4 \).
- The third inequality gives \( x \leq 5 \).